Press kit for the 2006 short Icelandic film "Family Reunion" (originally "Gódir gestir") (Elihu Burritt Library, Central Connecticut State University, 2006)
Press kit for the 2006 short Icelandic film "Family Reunion" (originally "Gódir gestir"), written and directed by Isold Uggadottir. Kit includes a plot synopsis, production notes, cast and crew bios, and a comprehensive cast and crew list. This film was shown at the 2007/20th Annual Connecticut Gay and Lesbian Film Festival.